1994
DOI: 10.1159/000129315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Conventional Highly Selective Vagotomy and Anterior Gastric Wall Stapling with Posterior Truncal Vagotomy on the Gastric Emptying Rate for Solid Meals in Beagle Dogs

Abstract: Anterior gastric wall stapling combined with posterior truncal vagotomy has been used as a new and adequate gastric acid output-reducing procedure. Severing the posterior vagal trunk as well as stapling the anterior gastric wall could impair gastric emptying. In this study, the gastric emptying rate for solid food, using a radionuclide technique, has been evaluated in 2 series of canine experiments. Compared to the results after conventional highly selective vagotomy, a temporary delay in the gastric emptying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This view is also substantiated by clinical [2,4] and motility [6] studies. The method used in this series was equally shown to adequately decrease gastric secretion in dogs, as well as in humans, without interfering with gastroduodenal motility [5,17], As to the pancreas, 25% of the fibers of the posterior vagal trunk are directed to this organ [18], either through the celiac plexus or directly through the posterior tract of Latarjet [ 19,20].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This view is also substantiated by clinical [2,4] and motility [6] studies. The method used in this series was equally shown to adequately decrease gastric secretion in dogs, as well as in humans, without interfering with gastroduodenal motility [5,17], As to the pancreas, 25% of the fibers of the posterior vagal trunk are directed to this organ [18], either through the celiac plexus or directly through the posterior tract of Latarjet [ 19,20].…”
Section: Discussionmentioning
confidence: 62%
“…In conclusion, the lack of postoperative diarrhea may not only be explained by a retained normal gastric motility, but also by virtually unaltered pancreatic enzyme secre tion after posterior vagal trunk section [2,4,6], PTV-AGS should, therefore, be considered a simplified and attractive alternative to high ly selective vagotomy in the treatment of chronic duodenal ulcer, avoiding some of the drawbacks of seromyotomy [5] and retaining the normal pancreatic function for up to 12 months after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No doubt the canine model has been for a long time preferred in the examinations of gastric emptying. Postoperative gastric emptying disorders in dogs involving the disruption of the stomach anterior wall was reported by Mistiaen et al [ 38 ] who using a radioisotopic technique showed a significant slowdown of gastric evacuation two weeks after the operative procedure. A co-ordination between the canine gastric and duodenal activity was reported by Ehrlein and Hiesinger [ 39 ].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, with anterior gastric stapling, perforation from too deep an incision during seromyotomy is avoided, while the completeness of intramural anterior vagotomy is guaranteed by sectioning all layers of the gastric wall. This technique has been shown to reduce gastric acid secretion adequately; radiologically and isotopically measured gastric emptying alters little [15,17]. Laparoscopic simplified alternatives to the time-consuming laparoscopic HSV such as parietal cell vagotomies (Taylor's and Hill-Barker's procedures) were already proposed to make the operation easier and faster [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%